2015
DOI: 10.1021/acs.jpca.5b00174
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics of Catechol (1,2-Benzenediol) and Guaiacol (2-Methoxyphenol) with Ozone

Abstract: The kinetic reactions of 1,2-benzenediol (catechol) and 2-methoxyphenol (guaiacol) with ozone were studied in a simulation chamber (8 m(3)) under dark conditions. The rate coefficients were measured at 294 ± 2 K, atmospheric pressure and dry conditions (relative humidity, RH < 1%), except for 1,2-benzenediol where they were also measured as a function of relative humidity (RH = 1-80%). The concentrations of organic compounds were followed by a PTR-ToF-MS for a continuous monitoring of gas-phase species. The O3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 35 publications
(93 reference statements)
7
50
0
Order By: Relevance
“…Methoxyphenols are semivolatile aromatic compounds with low molecular weight, and many of them are found to mainly exist in the gas phase at typical ambient temperature (Schauer et al, 2001;Simpson et al, 2005). Thus, methoxyphenols can be chemically transformed through gas-phase reactions with atmospheric oxidants (Coeur-Tourneur et al, 2010a;Lauraguais et al, 2012Lauraguais et al, , 2014aLauraguais et al, , b, 2015Lauraguais et al, , 2016Yang et al, 2016;Zhang et al, 2016;El Zein et al, 2015). The corresponding rate constants control their effectiveness as stable tracers for wood combustion and atmospheric lifetimes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Methoxyphenols are semivolatile aromatic compounds with low molecular weight, and many of them are found to mainly exist in the gas phase at typical ambient temperature (Schauer et al, 2001;Simpson et al, 2005). Thus, methoxyphenols can be chemically transformed through gas-phase reactions with atmospheric oxidants (Coeur-Tourneur et al, 2010a;Lauraguais et al, 2012Lauraguais et al, , 2014aLauraguais et al, , b, 2015Lauraguais et al, , 2016Yang et al, 2016;Zhang et al, 2016;El Zein et al, 2015). The corresponding rate constants control their effectiveness as stable tracers for wood combustion and atmospheric lifetimes.…”
mentioning
confidence: 99%
“…The corresponding rate constants control their effectiveness as stable tracers for wood combustion and atmospheric lifetimes. In recent years, the rate constants for the gas-phase reactions of some methoxyphenols with hydroxyl (OH) radicals (Coeur-Tourneur et al, 2010a;Lauraguais et al, 2012Lauraguais et al, , 2014bLauraguais et al, , 2015, nitrate (NO 3 ) radicals (Lauraguais et al, 2016;Yang et al, 2016;, chlorine atoms (Cl) (Lauraguais et al, 2014a), and ozone (O 3 ) (El Zein et al, 2015) have been determined. Some studies have indicated significant SOA formation from 2,6-dimethoxyphenol (syringol) and 2-methoxyphenol (guaiacol) with respect to their reactions with OH radicals (Sun et al, 2010;Lauraguais et al, 2012Lauraguais et al, , 2014bAhmad et al, 2017;Yee et al, 2013;Ofner et al, 2011).…”
mentioning
confidence: 99%
“…1 Syringol 9.6E-11 (Lauraguais et al, 2012) 4.0E-19 b (Zein et al, 2015) 2.6E+10 (O'Neill and Steenken, 1977) 3.6E+07 (Tratnyek and Hoigne, 1991a) 1.3E+04 c (Hoigné and Bader, 1983) 3.7E+09 (Kaur and Anastasio, 2018), (Smith et al, 2015) 2…”
Section: Details Of the Technique Are Discussed Inmentioning
confidence: 99%
“…Its emission factor of wood burning is in the range of 172−279 mg kg -1 fuel (Schauer et al, 2001). In recent years, the reactivity of gas-phase guaiacol toward OH radicals (Coeur-Tourneur et al, 2010a), NO3 radicals (Lauraguais et al, 2016;Yang et al, 2016), chlorine atom (Lauraguais et al, 2014a), and O3 (El Zein et al, 2015) has been investigated, suggesting that its degradation by OH radicals and NO3 radicals might be predominant Atmos. Chem.…”
Section: Introductionmentioning
confidence: 99%